2010
DOI: 10.2527/jas.2009-1976
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive performance and bone status markers of gilts and lactating sows supplemented with two different forms of vitamin D1

Abstract: In swine nutrition, little is known about the vitamin D requirements for reproductive processes and bone health. Consequently, the vitamin D recommendation for sows during gestation and lactation is not based on scientific reports. The current study was undertaken to obtain information on the dose-response pattern of 2 vitamin D sources, the commonly used cholecalciferol, called vitamin D(3), and a newly developed Hy.D product (25-hydroxycholecalciferol). In Exp. 1, a total of 160 gilts were randomly assigned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
67
3
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 24 publications
(34 reference statements)
8
67
3
3
Order By: Relevance
“…This suggests that a portion of the vitamin D 3 that is absorbed may be stored in adipose tissue rather than being transported to the liver for hydroxylation. The serum 25(OH) D 3 concentrations achieved in gestation from supplementing 25(OH)D 3 were less than those in the reports of previous researchers (Lauridsen et al, 2010;Coffey et al, 2012;Weber et al, 2014); this may be due to the time of sampling and duration of feeding, which Weber et al (2014) 1 In total 112 sows and litters were used to determine the effects of supplemental vitamin D from varying levels of vitamin D 3 or from synthetic 25(OH) D 3 on maternal performance, subsequent pig performance, sow and piglet serum vitamin metabolites, neonatal bone mineralization, and piglet muscle development. Means represent the average serum metabolite from 48 randomly selected litters (2 pigs per litter were bled for serum analysis) within treatments, and the same litters within each day were analyzed.…”
Section: Sow Serum 25(oh)d 3 Vitamin D 3 α-Tocopherol and Retinolcontrasting
confidence: 52%
See 1 more Smart Citation
“…This suggests that a portion of the vitamin D 3 that is absorbed may be stored in adipose tissue rather than being transported to the liver for hydroxylation. The serum 25(OH) D 3 concentrations achieved in gestation from supplementing 25(OH)D 3 were less than those in the reports of previous researchers (Lauridsen et al, 2010;Coffey et al, 2012;Weber et al, 2014); this may be due to the time of sampling and duration of feeding, which Weber et al (2014) 1 In total 112 sows and litters were used to determine the effects of supplemental vitamin D from varying levels of vitamin D 3 or from synthetic 25(OH) D 3 on maternal performance, subsequent pig performance, sow and piglet serum vitamin metabolites, neonatal bone mineralization, and piglet muscle development. Means represent the average serum metabolite from 48 randomly selected litters (2 pigs per litter were bled for serum analysis) within treatments, and the same litters within each day were analyzed.…”
Section: Sow Serum 25(oh)d 3 Vitamin D 3 α-Tocopherol and Retinolcontrasting
confidence: 52%
“…both vitamin D 3 and 25(OH)D 3 were added in diets at 2,000 IU of vitamin D (Lauridsen et al, 2010). This is because the vitamin D binding protein (chaperone protein for vitamin D metabolites in circulation) has a higher affinity for 25(OH)D 3 compared with vitamin D 3 (Bouillon et al, 1980).…”
mentioning
confidence: 99%
“…Therefore, the influence of feed intake is probably minimal. The fluctuations of bone formation and resorption observed in the present study are in accordance with fluctuations around parturition found in cows (Naito et al, 1990;Peterson et al, 2005;Ekelund et al, 2006), sows (Liesegang et al, 2005;Counotte et al, 2009;Lauridsen et al, 2010;Cools et al, 2014), and goats and sheep (Farrugia et al, 1989;Liesegang et al, 2006 and.…”
Section: Discussionsupporting
confidence: 92%
“…The maternal and nursery vitamin D treatment impacts on growing pig serum 25(OH)D 3 in this study were largely expected. Most previous reports (Lauridsen et al, 2010;Witschi et al, 2011;Coffey et al, 2012;Weber et al, 2014) have all shown that supplementation of 25(OH)D 3 at the same IU equivalency of vitamin D 3 will result in an increased serum 25(OH) D 3 response. Also, increasing maternal vitamin D 3 supplementation has been shown to lead to an increase in subsequent pig serum 25(OH)D 3 (Flohr et al, 2014a), which is consistent with results from the current study.…”
Section: Discussionmentioning
confidence: 99%